Case Study: Bissau-Guinean farmers train their cameras on a protected area - Roque de Pinho, Joana (Visual Research: A Concise Introduction to Thinking Visually. Second Edition, 2023)
Visual Research: A Concise Introduction to Thinking Visually, Second Edition, provides an accessible introduction to doing visual research in the social sciences. Beginning with ethical considerations, this book highlights the importance of thinking visually before engaging in visual research. Further themes involve creating, organizing, and using images and are presented so as to help readers think about and work with their own visual data. © 2024 Jerome W. Crowder and Jonathan S. Marion. All rights reserved.